mw - t = 2w + 5, for W
You will see that this is really easy. Just follow this method:
1. Rearrange equation to have like terms on the same side:
- All terms with the same variable go on the same side
- Any terms with a unique variable goes with the constants
So, we have:
$\displaystyle mw - t = 2w + 5$
Subtract 5 from both sides:
$\displaystyle mw - t - 5 = 2w + 5 - 5$
$\displaystyle mw - t - 5 = 2w$
Subtract mw from both sides:
$\displaystyle mw - t - 5 - mw = 2w - mw$
$\displaystyle t - 5 = 2w - mw$
2. Factor out a w on the right side of the equation:
$\displaystyle t - 5 = w(2 - m)$
Divide both sides by 2 - m:
$\displaystyle \frac{t - 5}{2 - m} = \frac{w(2 - m)}{2 - m}$
$\displaystyle \frac{t - 5}{2 - m} = w$
And there you are.